Hemodynamic Stability via Ultrasound-Guided Axillary Brachial Plexus Block with Levobupivacaine-Dexamethasone in a Patient with Impending Thyroid Storm and Hand Fracture - Anak Agung Ngurah Aryawangsa (HM Publisher, 2026)
The perioperative management of patients with uncontrolled hyperthyroidism requiring emergency surgery presents an acute clinical challenge, as surgical trauma and anesthesia can precipitate a life-threatening thyroid storm. This case report examines the strategic role of regional anesthesia in mitigating such risks through complete afferent blockade and sympathetic stabilization. A 28-year-old male presented with multiple right-hand fractures following a motorcycle accident. The patient had a history of untreated hyperthyroidism for one year and exhibited classic clinical thyrotoxicosis, including tachycardia of 104 bpm, hypertension of 164/90 mmHg, bilateral exophthalmos, and hyperkinesis. Laboratory investigations confirmed primary hyperthyroidism with a markedly elevated free T4 of 86.6 pmol/L and suppressed TSH. His Burch-Wartofsky Point Scale (BWPS) score was calculated at 30, indicating an impending thyroid storm. Following rapid medical optimization with propylthiouracil, propranolol, hydrocortisone, and amlodipine, surgical intervention was successfully performed under ultrasound-guided axillary brachial plexus block. The anesthetic mixture comprised 20 mL of 0.5 percent levobupivacaine and 8 mg of perineural dexamethasone. The patient demonstrated remarkable hemodynamic stability throughout the two-hour procedure, maintaining a systolic blood pressure between 115 and 135 mmHg and a heart rate between 82 and 94 bpm, without progressing to a thyroid crisis. In conclusion, ultrasound-guided regional anesthesia, specifically the axillary approach, offers a superior safety profile for thyrotoxic patients by avoiding airway instrumentation and preventing the sympathetic surges associated with general anesthesia. The synergistic use of levobupivacaine and dexamethasone provides a dual benefit of enhanced cardiac safety and peripheral endocrine stabilization.